Fenomena Mualaf Selebriti Keturunan Tionghoa-Indonesia: Identitas, Media, dan Wacana Islamisasi: The Phenomenon of Chinese-Indonesian Celebrity Converts: Identity, Media, and the Discourse of Islamisation - Ahmad Musadad; Firman Setiawan; Achmad Badarus Syamsi; Misno Misno; Saifudin Amin; Tri Pujiati (STAIN Sultan Abdurrahman Kepulauan Riau, 2026)
The increasing number of Chinese-Indonesian celebrities converting to Islam has emerged as a prominent phenomenon and serves as the backdrop for this study. The primary objective of this research is to analyze how this event is represented in digital media and its relationship to the construction of identity and the discourse of Islamization in contemporary Indonesia. This study examines the representation of religious conversion by Chinese-Indonesian celebrities in digital media, with the scope of analysis focusing on the formation of identity and Islamization discourse, specifically exploring how media constructs and disseminates narratives of conversion through images, articles, and news coverage. The study adopts the theoretical approach of Critical Discourse Analysis (CDA), integrating the perspectives of Social Identity Theory, Representation Theory, and Discourse Theory. The findings reveal that religious conversion is not merely a personal choice but also a social strategy to navigate the dynamics between majority and minority groups. Key findings indicate that the converts transition from an out-group position (Chinese and non-Muslim minorities) to an in-group position (Muslim majority) to gain legitimacy and social acceptance. Media plays a central role in constructing their stories as heroic narratives that reinforce the hegemony of Islam, depicting the conversion process as a spiritual journey marked by sacrifice and triumph. The discourse produced not only generates knowledge about the “truth” of Islam but also creates a subject position that functions as “living proof” of Islam's inclusivity. Practically, this study demonstrates how performative phenomena in digital spaces serve as instruments to affirm social norms and religious ideologies.